The negative image of Islamic resurgence in the West: myth or reality? - Abu Shouk, Ahmed Ibrahim (IIUM Press, 2009)
The current war in Afghanistan and Iraq is justified by Western policymakers as a war on terrorism rather than being a war between the West and Islam. The justification is taken at its face value by some Muslim leaders and clients of the West in the Muslim world, while Muslim activists consider it as a superficial justification that does not rationalize the declaration of war on terrorism as not a war against Islam. Anyone who reads Samuel P. Huntington’s book The Clash of Civilizations and the Remaking of the World Order will realize that the ongoing war in the Muslim world is indeed a war against Islam. It is not simply a criminal prosecution against terrorists, but a fundamental clash between the “democratic west” and the Islamic East. The aim of this paper is to examine the factors that painted the picture of the West in the Muslim world, and discuss the reasons that shaped the negative image of Islamic resurgence and Islam in the West. It also addresses the issue of how to boost the image of Islam in the West, where it has already been equated with terrorism and violence.